Beneficial and biocontrol effects of Trichoderma atroviride, a dominant species in white birch rhizosphere soil - Liu, Kuo; Zhang, Yu-Zhou; Du, Hua-Ying; Wang, Zhi-Ying; Gu, Pei-Wen; Liu, Zhi-Hua; Yu, Ze-Yang (Frontiers in Microbiology, 2023)
White birch (Betula platyphylla Suk.) is a typical pioneer tree species that is important in forest restoration in northern China, Japan and Korea. In the present study, 37 isolates were obtained from B. platyphylla rhizosphere soils in Heilongjiang Province; they were identified as T. pleuroticola (3 isolates), T. virens (2 isolates), T. hamatum (8 isolates), T. atroviride (21 isolates, dominant species) and T. asperelloides (3 isolates). Stress tolerance tests (salt, alkali and nutritional stress that simulated saline alkali or barren soil) and confrontation assays (with four pathogens) were performed to determine which isolates had good biocontrol ability in barren soil; the results show that T. atroviride was outstanding. Then, in order to determine the effect of T. atroviride on plants and soil, Gynura cusimbua seeds were sown and treated with T. atroviride spore suspension, as was unsown soil. The seedlings treated using T. atroviride had significantly greater height, stem diameter, soluble protein content, soluble sugar content and malonaldehyde (MDA) content; their catalase (CAT) activity was also significantly increased. In addition, when the plants were inoculated with Alternaria alternata, the plants treated using T. atroviride had stronger CAT activity, significantly higher soluble protein content and soluble sugar content, and significantly lower MDA content, which indicates stronger resistance and less injury caused by the pathogen. In addition, T.atroviride not only increased the content of available nitrogen and available phosphorus in the soil, but also promoted the G. cusimbua seedlings' absorption of available nitrogen and available phosphorus. Thus, the characteristics of T. atroviride may make it the main factor that helps B. platyphylla colonize cut-over lands. T. atroviride, a promising biocontrol candidate, can be used in agriculture and forestry.